Screening of osteoporosis using calcaneal quantitative ultrasound in a rural population of Jammu, Jammu and Kashmir, India - Gupta, Rishabh; Mahajan, Shavi; Dewan, Deepika; Gupta, Rajat (International Journal Of Community Medicine And Public Health, 2017)
Background: Osteoporosis is a major public health problem, associated with substantial morbidity and socio-economic burden. The objective of the present study was to screen the general population for osteoporosis in a rural area of Jammu region. Methods: 3 screening camps were conducted at 6 monthly intervals between the time period 2015-2016, at the Accidental Hospital, Chowki Choura, which is a rural area of district Jammu, J&K. A total of 270 subjects in the age group 20 to 80 years were subjected to screening through BMD measurements using calcaneal QUS and they were analyzed on the basis of T-scores. Results: Out of 270 subjects, 120 were males and 150 were females. Among 120 males, 68 were in the age group of 20 - 49 years, and 52 were above 50 years. In the age group 20-49 years, 26 males (38.2%) had osteopenia, and 4 (5.9%) had osteoporosis. In males above 50 years of age, 35 (67.3%) had osteopenia and 6 (11.5%) had osteoporosis. Out of 150 females, 94 were in the age groups 20-49 years, and 56 were above 50 years of age. In the age group 20-49 years, 51 females (54.3%) had osteopenia and 12 (12.8%) had osteoporosis. In females above 50 years of age, 32 (57.1%) had osteopenia and 15 (26.8%) had osteoporosis. Conclusions: The overall prevalence of osteoporosis among screened population was 13.7%. It increased with age in both males and females; however the prevalence of osteoporosis was more among females as compared to males (18% vs. 8.3% respectively).